2007
DOI: 10.1677/joe-07-0126
|View full text |Cite
|
Sign up to set email alerts
|

GH enhances proliferation of human hepatocytes grafted into immunodeficient mice with damaged liver

Abstract: We investigated effects of human (h) GH on the proliferation of h-hepatocytes that had been engrafted in the liver of albumin enhancer/promoter driven-urokinase plasminogen activator transgenic/severe combined immunodeficiency disease (uPA/SCID) mice (chimeric mice). The h-hepatocytes therein were considered to be deficient in GH, because hGH receptor (hGHR) is unresponsive to mouse GH. Actually, hIGF-1 was undetectable in chimeric mouse sera. The uPA/SCID mice were transplanted with h-hepatocytes from a 6-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Recently, we showed that h-hepatocytes in h-hep-mice are growth hormone-deficient, because mouse growth hormone does not recognize the human growth hormone receptor of h-hepatocytes. 37 However, we consider that h-hepatocytes would be able to respond to TGF-␤ if the host m-HSCs secreted it, because there has been no report of species specificity between h-and m-TGF-␤. In the present study we clearly demonstrated the coincidence of lack of TGF-␤/TGFBR signaling with the hyperplasia of h-hepmouse liver.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that h-hepatocytes in h-hep-mice are growth hormone-deficient, because mouse growth hormone does not recognize the human growth hormone receptor of h-hepatocytes. 37 However, we consider that h-hepatocytes would be able to respond to TGF-␤ if the host m-HSCs secreted it, because there has been no report of species specificity between h-and m-TGF-␤. In the present study we clearly demonstrated the coincidence of lack of TGF-␤/TGFBR signaling with the hyperplasia of h-hepmouse liver.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, human hepatocytes in the livers of chimeric mice are susceptible to growth enhancing activities. The treatment of chimeric mice with human growth hormone (hGH) increases the repopulation speed and the replacement index of transplanted human hepatocytes, as determined by increased replicative DNA synthesis and the up-regulation of hGH-related signalling molecules (Masumoto et al, 2007). Furthermore, treatment with epidermal growth factor (Yamada et al, 2014) and partial hepatectomy (personal communication, Dr. Chise Tateno) also enhances hepatocellular proliferation in this chimeric mouse model.…”
Section: Epsilon-momfluorothrinmentioning
confidence: 98%
“…Information on the donors of the hepatocyte preparations used is presented in Table 1. Hepatocytes from these three donors were selected for transplantation because cells from young subjects are more responsive to the stimulation of hepatocellular proliferation (Masumoto et al, 2007). For the purposes of transplantation, vials of cryopreserved human hepatocytes (5-10 x 10 6 cells/vial) were thawed and transplanted into 20-60 cDNA-uPA/SCID mice (2.5 x 10 5 viable cells/ mouse).…”
Section: Chimeric Mouse Study Animalsmentioning
confidence: 99%
“…4 -6 ( Table 2)], three chimeric mice with hepatocytes 6YF [nos. 4 -6 ( Table 2)], one chimeric mouse 9MM (not included in Table 2), and one chimeric mouse 6YF (not included in Table 2) were continuously infused with 2.5 mg/kg⅐d h-GH (Wako, Osaka, Japan) through an sc-implanted Alzet micro-osmotic pump (Alza Corp., Palo Alto, CA) for 2 wk before killing (6,17). Blood h-albumin (Alb) and serum h-IGF-I in the mice were quantified as previously reported (6).…”
Section: Animals Transplantation Of H-hepatocytes and Treatment Of mentioning
confidence: 99%
“…However, we noticed that the mice spontaneously developed hepatic steatosis as the time after transplantation was prolonged. The h-hepatocytes of a chimeric mouse are in a GH-deficient state (6) primarily because human cells do not react with rodent GH (7), thus suggesting that the observed lipid accumulation in h-hepatocytes was caused by a lack of available h-GH in chimeric mice.…”
mentioning
confidence: 99%